Niewydolność serca i płuc, transplantologiaPrognosis of patients with advanced heart failure referred for heart transplantation – data of POLKARD heart failure registry 2003–2005 - Korewicki, Jerzy; Browarek, Aldona; Zieliński, Tomasz; Sobieszczańska-Małek, Małgorzata; Piotrowska, Małgorzata; Zembala, Marian; Zakliczyński, Michał; Rozentryt, Piotr; Barańska-Kosakowska, Anna; Sadowski, Jerzy; Przybyłowski, Piotr; Milaniak, Irena; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: A decrease in mortality of patients with heart failure has been observed during recent years and the availability of hearts for transplantation is still sparse. This underlines the necessity of an appropriate choice of possible therapies. A prospective registry of patients referred for heart transplantation in all four transplant centres in Poland was conducted from 2003 to 2005. Aim: The goal of the registry was to determine the survival of patients referred for heart transplantation (OHT) and the risk factors including Aaronson (HFSS) score, NT-proBNP levels, and hs CRP. Materials and methods: Patients were recruited from the fourth quarter of 2003 to the end of the third quarter of 2005. Observation time was 3 to 22 months. During that period 675 pts aged 18-65 (87% men) with severe heart failure (74% – IIII or IV NYHA class) were referred to transplant centres for heart transplant evaluation. From 675 after evaluation 335 (49.6%) were enlisted on the waiting list for OHT, between them 10.7% as super urgent, 9% urgent and the rest as planned. Patients qualified as super urgent and urgent were characterized by higher heart frequency, higher NTproBNP levels, lower blood pressure, and lower Aaronson (HFSS) values as compared to qualified as planned. Mortality in the whole group was 15.3%, in those pts in whom transplantation was judged not yet needed 5.4%. In patients enlisted for OHT mortality was 19.4% for qualified as super urgent, 16.5 % for urgent and 7.4% for planned. Results: During the registry observation 142 pts were transplanted, 30.9% died, between them a majority with ischaemic heart disease. In qualified as super urgent 55% died, in urgent 23.8%, in qualified as planned mortality was 30%. Conclusions: Important differences in Aaronson (HFSS) score, NTproBNP levels and spiroergometric test results were noted between centres involved in the registry for patients enlisted.